2022
DOI: 10.7860/jcdr/2022/58107.17050
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Survey of E-learning Readiness and Academic Performance among Nursing Students in Saudi Arabia

Abstract: Introduction: Determining students’ readiness for e-learning is critical to implementing more effective education and performance. Nursing education in Saudi Arabia continues to struggle with a shortage of technical tools to enable teaching and acquiring critical nursing skills. Aim: To assess the level of e-learning readiness and academic performance and their association in nursing students and to determine the factors associated with e-learning readiness and academic performance. Materials and Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… Full distance learning approach is an effective approach; however, appropriate awareness is necessary to be raised. INNAB et al 31 The study has aimed to identify E-learning Readiness and Academic Performance among nursing students in Saudi Arabia Quantitative survey Private universities of Saudi Arabia 139 nursing students have been selected to collect data. The survey has identified that the students are ready for e-learning approach because their academic performance is improving.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Full distance learning approach is an effective approach; however, appropriate awareness is necessary to be raised. INNAB et al 31 The study has aimed to identify E-learning Readiness and Academic Performance among nursing students in Saudi Arabia Quantitative survey Private universities of Saudi Arabia 139 nursing students have been selected to collect data. The survey has identified that the students are ready for e-learning approach because their academic performance is improving.…”
Section: Resultsmentioning
confidence: 99%
“… 29 Some students feel that e-learning does not provide the same level of support and engagement as traditional classroom learning. 28 , 31 Additionally, some students may experience technical difficulties or may lack the necessary technology or internet connection to access e-learning resources. About 61.5% of the students who participated expressed dissatisfaction with their e-learning experience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation